Parsonage-Turner syndrome, an unusual infant impairment - A case report and review of literature - F. A. B. Garcia; G. R. L. Barroso (Scientific Electronic Archives, 2018)
The Parsonage-Turner Syndrome, also known as Neuralgic Amyotrophy, is classified as a plexopathy. A multifactorial arrangement of trigger factors are proposed, including traumatic injury and an autoimmune hypothesis. Treatment still lays on the empirical practice and the preventive measure is unclear and not available. The objectives of this article is describing an unusual case report of a patient, female, 12-years-old, who was diagnosed with Parsonage-Turner Syndrome, and more important, to display the fact that not only young adults and elderly individuals are predisposed to develop this injury.